Natural Gums Emphasized Grafting Technique: Applications and Perspectives in Floating Drug Delivery System - Sah, Sushil Kumar (Asian Journal of Pharmaceutics (AJP), 2016)
Polymers play a very pompous role in each and every morsel of lives. Intentionally or unintentionally, each and every personality at present depends on the polymer to get together various requirements. According to their characteristics, polymers are even not accomplishing the bid if it is abundant at times. Due to advancement in polymer science, it is vital in the future prospective as they can improve the range of applications in the floating drug delivery system. Due to modification of various techniques in the floating drug delivery system, the grafting of polymers has gained much more aggravated for the production of new monomers to transport polymeric materials from one region to another region in the body. In short, the modification is crucial to face and stand against various challenges because it is hard to obtain new polymers. Sometimes, harmonization of properties is required which can be achieved via modification of polymers. The modification is needed to fetch precise properties to material which is to be modified such as enhanced stability, compatibility, flexibility, and rigidity. This review highlights the various grafting technique which will help for the grafting modification by the use of natural gums in floating drug delivery.